Ultra-soft organic combined film with piezoelectricity induced by liquid-liquid interface polar engineering - Yongkang Zhang; Xiaonan Hu; Zhaonan Yan; Siyu Zhang; Jiling Zhao; Hao Sun; Shuhai Liu; Yong Qin (Nature Communications)
Abstract Although organic piezoelectric materials are increasingly being studied in the field of biomechanical sensing, the combination of high piezoelectricity and high softness is still a huge challenge due to the existence of steric hindrance effect. To conquer this, a polar engineering utilizing liquid-liquid interface induced orientation is developed. It induces polar asymmetry in two linear polymers (polystyrene-block-polyisoprene-block-polystyrene/polyethylene glycol, PEG/SIS) with low steric hindrance through a polar interface, thereby achieving high piezoelectricity in a soft material system. This PEG/SIS combined film not only exhibits a piezoelectric coefficient as high as 22.9 pC/N, and stable performance, without attenuation for 60 days, which is comparable to the piezoelectricity of the natural organic materials PVDF, but also has an ultra-softness (~1 × 10–6 Pa–1) similar to that of skin, cartilage and aorta, showing high mechanical compliance with biological tissues. This work gives an approach for the development of organic piezoelectric materials, and is expected to achieve large-scale production and application of highly sensitive flexible biomechanical sensors on various surfaces and in vivo environments.